2013
DOI: 10.1038/emm.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnogalacturonan II is a Toll-like receptor 4 agonist that inhibits tumor growth by activating dendritic cell-mediated CD8+ T cells

Abstract: We evaluated the effectiveness of rhamnogalacturonan II (RG-II)-stimulated bone marrow-derived dendritic cells (BMDCs) vaccination on the induction of antitumor immunity in a mouse lymphoma model using EG7-lymphoma cells expressing ovalbumin (OVA). BMDCs treated with RG-II had an activated phenotype. RG-II induced interleukin (IL)-12, IL-1β, tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) production during dendritic cell (DC) maturation. BMDCs stimulated with RG-II facilitate the proliferation of CD8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…Further findings from the in vivo study using transgenic mouse model supported the notion that the RG could have activated DC through Toll like receptor 4 , resulting in phenotypic maturation of DC and activation of mitogen-activated protein kinase (MAPK) signal pathway. The study also demonstrated successful targeting and ultimately, inhibition of EG7 lymphoma cell growth ( Park et al, 2013 ). Therefore, it is worthy for us to explore into the feasibility to use RG as a natural drug product to prevent gastric cancer formation as a result of H. pylori infection, and study the possible mechanisms involved in the suppression of gastric cancer cells before advancement to later stages.…”
Section: Polysaccharidesmentioning
confidence: 90%
See 1 more Smart Citation
“…Further findings from the in vivo study using transgenic mouse model supported the notion that the RG could have activated DC through Toll like receptor 4 , resulting in phenotypic maturation of DC and activation of mitogen-activated protein kinase (MAPK) signal pathway. The study also demonstrated successful targeting and ultimately, inhibition of EG7 lymphoma cell growth ( Park et al, 2013 ). Therefore, it is worthy for us to explore into the feasibility to use RG as a natural drug product to prevent gastric cancer formation as a result of H. pylori infection, and study the possible mechanisms involved in the suppression of gastric cancer cells before advancement to later stages.…”
Section: Polysaccharidesmentioning
confidence: 90%
“…However, RG seems capable of eliciting sufficient immune responses to eradicate tumor cells. For instance, in a study conducted by Park et al (2013) , a ramified form of RG (RG-2) extracts from Panax ginseng were able to enhance antigen presentation and stimulatory capability of dendritic cells to CD8+ T-lymphocytes after priming with ovalbumin-expressing EL-4 (EG7) tumor cells. Further findings from the in vivo study using transgenic mouse model supported the notion that the RG could have activated DC through Toll like receptor 4 , resulting in phenotypic maturation of DC and activation of mitogen-activated protein kinase (MAPK) signal pathway.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…For example, a RG-II-type polysaccharide isolated from mature leaves of green tea, presented antitumor and anti-metastatic activities via activation of macrophages and natural killer cells [52]. RG-II isolated from the leaves of Panax ginseng inhibited tumor growth by activating dendritic cell-mediated CD8 + T cells [53]. Furthermore, a RG-I domain-rich pectin from potato inhibited the proliferation of HT-29 cells and induced significant G2/M cell cycle arrest [54].…”
Section: Antiproliferative and Cytotoxic Actions Of The Yerba Mate Pomentioning
confidence: 99%
“…The canonical Toll-like receptor 4 (TLR4) signaling cascade is initiated when lipid A (the membrane anchor of lipopolysaccharide [LPS]) is bound by the extracellular region of CD14, which complexes with MD2 and binds to membrane-bound TLR4 ( 46 ). Dimerization of these molecules with another lipid A-MD2-TLR4 complex creates a functional TLR4 signaling complex ( 47 ). Binding of a TLR4 agonist like lipid A initiates an innate immune response that can drive the development of antigen-specific acquired immunity ( 48 ).…”
Section: Interplay Between Tlr4 and Fatty Acid Metabolismmentioning
confidence: 99%